Identification of proteins in Candidatus Liberibacter asiaticus to develop an immunoenzymatic detection method - Rodríguez-Quibrera, Cynthia Guadalupe; Almeyda-León, Isidro Humberto; Flores de la Rosa, Felipe Roberto; Hernández-Mendoza, José Luis; Cruz-Hernández, María Antonia; Mendoza-Herrera, Alberto (Revista Mexicana de Ciencias Agrícolas, 2022)
The objective of this work was to identify outer membrane proteins in the genome of Candidatus Liberibacter asiaticus (CLas) with potential for the development and optimization of an immunoenzymatic detection method. The study was conducted during 2019, and the Predict Protein web server, as well as the HhPred/HhSearch and Pfam databases, were used. Fifty-two outer membrane proteins were detected in the complete genome of CLas, of which 11 had not been previously characterized. Predictive analyses performed on the protein B8Y674 generated eight possible epitopes and four of them, experimentally evaluated in B cells, showed percentages of identity between 80 to 90%. CLas was detected by endpoint PCR from DNA extracted from Mexican lime with symptoms of Huanglongbing using primers designed on the sequence of the Omp gene encoding the protein B8Y674 and 95% identity was recorded between the generated sequences and sequences of CLas previously reported. The results obtained allow us to infer that the protein B8Y674 is a potential candidate to be used in the immunoenzymatic detection of CLas.